PENGARUH KEMAJUAN TEKNOLOGI TERHADAP HUKUM DAN PERUBAHAN SOSIAL - TITIN TITAWATI; ALINE FEBRIANY LOILEWEN; GEDE TUSAN ARDIKA; RAMLI RAMLI (GANEC SWARA, 2024)
Research would like to explain that progress in the field of technology is very rapid, this is proven by the many changes that we feel, such as matters related to the legal field and also social changes, all of which are helped and made easier by the existence of technology which is sufficient to support all our activities in adult life. This. In the legal sector, for example: we can now see or review the trial process in court directly online with the e-court application. This includes e-Filing (online case registration at court), e-Payment (online down payment of case fees), e -Summons (online summoning of parties) this makes it easier where litigants can also see the trial schedule online, where this can save time in daily activities,